Penetapan Harga Pokok Produksi Kacang Koro Pedang pada UD Laksmi Devi - WIDYANTARI, NI WAYAN LIA; SUAMBA, I KETUT; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.1, Januari 2018DO - 10.24843/JAA.2018.v07.i01.p04, 2018)
Determination of Cost of Goods Manufactured of Jack Beans on UD Laksmi Devi UD Laksmi Devi is an agro-industrial processing of jack beans. The business competition is high, so it is necessary to establish the appropriate best selling price of product through analysis of cost of goods manufactured price of jack beans. This study aims to find out the cost of jack beans manufactured by UD Laksmi Devi, The result of calculation of the cost of goods manufactured based on the components of production costs and non-production costs, compare the difference in the calculation of cost of production from both analysis, and show sensitivity of cost to cost of goods of jack beans manufactured with sensitivity analysis. Analysis of cost of goods manufactured are calculated only one month, namely December 2016. Calculation of the cost of goods manufactured per unit by UD Laksmi Devi Rp 28.887,33, while the value through the analysis of cost of goods manufactured that takes into account the components of production and non-production costs amount to Rp 31.529,83. Component of costs incurred by UD Laksmi Devi only production costs, making it look bigger profits of Rp 22.005.612, compared by researched in the analysis of cost of goods manuafactured only Rp 12.492.612. The difference shows that the analysis of cost of goods manufactured based on production costs and non-production costs is good to applicate because the costs are detailed, so the cost of good manufactured are accurate as the basic for determining the selling price of jack beans in UD Laksmi Devi.